Technogenic change of the geological environment of urban areas (by the example of Irkutsk town) - Kadetova, A. V.; Rybchenko, A. A.; Trzhcinsky, Yu. B. (Bulletin of the Geological Society of Greece, 2007)
The paper discusses engineering-geological problems of urban areas, among which are geohazards like flooding, suffosion subsidence, erosion, and gravitation. It is the concern of the research to do both natural and industrial effect analyses. A detailed historical-geological evaluation has been made of urban spatial development as one of the main geological environment modification factors